Inverting nutrient fluxes across the land-water interface – Exploring the potential of zebra mussel (Dreissena polymorpha) farming. (1st March 2021) - Goedkoop, Willem; Choudhury, Maidul I.; Lau, Danny C.P.; Grandin, Ulf
Abstract: We studied the potential of zebra mussel farming for nutrient retention in a eutrophic lake. Duplicate experimental long-line cultivation units were deployed and mussel growth and nutrient retention were quantified after 28 months. Mussels grew well at shallow water depth (<3 m) and our 625 m 2 (lake area) experimental units produced 507 and 730 kg dry biomass, respectively, of which 94% were shells. These yields corresponded to an average retention of 92.7 ± 23.1 kg C, 6.1 ± 0.68 kg N, and 0.43 ± 0.04 kg P retention, or 742 kg C, 49 kg N, and 3.5 kg P for a full-size (0.5 ha) mussel farm. We estimate that concentrating the long-lines to a depth of 2.5 m would probably have doubled these yields, based on the differences in mussel growth among depths. We further estimate that a full-size cultivation unit (0.5 ha) thus could compensate for the annual total-P run-off from 23 ha, or the biologically available P from approximately 49 ha of agricultural soils. As traditional measures have proven insufficient, decision-makers need to facilitate novel approaches to mitigate the negative effects of cultural eutrophication. We envision that zebra mussel farming, within their invaded range, provides a promising approach to invert nutrient losses in lakes and coastal lagoons. Highlights: Zebra mussel cultivation units produced between 507 and 730 kg dry biomass, of which 94% shells. 0.5 ha of mussel cultivation can compensate for the bioavailable P from 49 ha of agricultural soils. Zebra mussel farming is a promising approach to invert nutrient losses to lakes and coastal lagoons. Zebra mussel can only be applied in the species' invaded range. Abstract : Zebra mussel cultivation efficiently traps highly bioavailable nutrients, thereby inverting the flux of nutrient from land to water, alleviating cultural eutrophication, and improving water quality.